2008
DOI: 10.1136/jech.2007.062240
|View full text |Cite
|
Sign up to set email alerts
|

Impact of parity on anthropometric measures of obesity controlling by multiple confounders: a cross-sectional study in Chilean women

Abstract: Parity modestly influences BMI, but does not seem to be related to WC, WHR and WHtR after controlling by confounders. Parity can increase adiposity but not necessarily following an abdominal pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
46
4
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 79 publications
11
46
4
4
Order By: Relevance
“…Compared to nulliparous women, the risk of obesity rises 5.8-fold among mothers with parity of 4 or more and 2.6-fold with 2 or 3 pregnancies. This agrees with other studies [18][19][20]. The increased parity of women in higher BMI categories may be related to the tendency to gain weight with each pregnancy [19].…”
Section: Discussionsupporting
confidence: 82%
“…Compared to nulliparous women, the risk of obesity rises 5.8-fold among mothers with parity of 4 or more and 2.6-fold with 2 or 3 pregnancies. This agrees with other studies [18][19][20]. The increased parity of women in higher BMI categories may be related to the tendency to gain weight with each pregnancy [19].…”
Section: Discussionsupporting
confidence: 82%
“…Parity was positively associated with obesity in our population, independent of age. Several other studies in the region 12,25,28,29 have reported similar results. Although higher parity is sometimes considered an indicator of lower SES, pregnancy-related weight retention independent of various sociobehavioral factors is well documented.…”
Section: Obesity and Body Image In Colombian Womensupporting
confidence: 79%
“…2 The associations of SES indicators with overweight and obesity in our study are consistent with those from other studies among Latin American women of low-income groups within their countries. 10,25 The positive association between SES indicators and overweight=obesity based on BMI found in our study may be due to a shift away from a traditional diet, as women with greater purchasing power may have increased access to processed foods that are high in saturated fat and refined carbohydrates. 26 The presence of nonnegligible rates of obesity in all SES categories, with a greater burden in the highest SES groups, is typical of countries in middle stages of economic development.…”
Section: Discussionmentioning
confidence: 82%
“…Además, se advierte que el IMC logra un porcentaje más alto de concordancia de clasificación con el PC tanto para el criterio de la OMS para "riesgo sustancialmente incrementado" (PC > 88 cm) (20), como por la propuesta de Koch y cols. (PC > 87,7 cm) (21). Sin embargo, la mayor similitud entre los valores de sensibilidad y especificidad se da con el ICC considerando el criterio de la OMS (20).…”
Section: Resultsunclassified